Pengaruh Stigmatisasi Sosial Terhadap Koping Stress Perawat Dalam Penanganan Covid-19 : The Effect of Social Stigmatization on Nurses' Stress Coping in Handling Covid-19 - Tri Winugroho; Arief Budiarto; Sarpono; Arip Hidayat (Fakultas Keperawatan Universitas Andalas, 2021)
During the Covid-19 pandemic, Indonesia also faced a tendency to increase the number of cases. Stigma that arises from the community both to patients and health workers will actually have an impact on nurses' psychology such as feelings of guilt, anxiety, fear, feeling as a source of disease transmission. The purpose of this study was to analyze the effect of social stigma on nurses' coping with stress in handling Covid-19. This study used a correlative quantitative approach with a sample of 101 nurses. Questionnaires are used as instruments in data collection. This study uses the SPSS 20 application to perform statistical tests in the analysis. The results of the study can be concluded that the probability number obtained is p of 0.015 < from the value of (0.05) then this means that the emergence of social stigma affects nurses' coping stress in handling COVID-19. The figure of the coefficient of determination (r square) means that Social stigma variable affects coping stress in handling covid-19 at Tk II Hospital dr. Soedjono Magelang by 5.9%, while the remaining 94.1% is influenced by other variables outside of factors or variables that are not examined. Further research is needed, especially factors that were not investigated in this study such as gender, age, education, and social support.